083 Intravenous magnesium for acute presentations of migraine to A&E. Issue 9 (12th August 2022) - Laurente, Raphael; See, Isaiah; Lane, Charlie; Alim-Marvasti, Ali; Balaratnam, Michelle; Chandratheva, Arvind; Matharu, Manjit; Simister, Robert; Kamourieh, Salwa; Haider, Salman
Abstract : Background and aim: Studies have demonstrated the role of magnesium on acute migraine attacks and prophylaxis via voltage-dependent blockade of N-methyl-D-aspartate (NMDA)-coupled channels. Our aim was to study the tolerability of intravenous (IV) magnesium in the treatment of migraine in the Emergency Department (ED) and the Same Day Emergency Care (SDEC) unit of University College Hospital, London. Methods: We performed a non-randomised open-label trial to establish the safety of IV magnesium sulfate. Patients were recruited from the ED or the SDEC unit of the hospital after being reviewed by consultant Neurologists from Aug 2021 – Jan 2022. Magnesium levels were measured prior to administration of the drug and complications were closely monitored. Results: 35 patients with status migrainosus were recruited; 30 were females and their mean age was 39 years (SD: 13.5 in years). All had normal serum magnesium levels prior to drug administration. No ECG changes were identified. None developed serious adverse symptoms during or immediately after infusion. A beneficial effect was noted in 15 patients, no effect in 10, and missing data in 10. Conclusion: Administration of IV Magnesium is an effective and tolerated adjunct for the management of migraine. Efficacy studies are currently underway.